Transdentinal cell photobiomodulation using different wavelengths - Turrioni, Ana Paula Silveira [UNESP]; Basso, Fernanda Gonçalves [UNESP]; Alonso, Juliana Rosa Luiz [UNESP]; De Oliveira, Camila Fávero; Hebling, Josimeri [UNESP]; Bagnato, Vanderlei S.; Costa, Carlos Alberto de Souza [UNESP] (Operative Dentistry, 2015)
Objective: The aim of this study was to investigate the effects of transdentinal irradiation with different light-emitting diode(LED) parameters on odontoblast-like cells (MDPC-23). Methods and Materials: Human dentin discs (0.2 mm thick) were obtained, and cells were seeded on their pulp surfaces with complete culture medium (Dulbecco modified Eagle medium). Discs were irradiated from the occlusal surfaces with LED at different wavelengths (450, 630, and 840 nm) and energy densities (0, 4, and 25 J/cm2 ). Cell viability (methyltetrazolium assay), alkaline phosphatase activity (ALP), total protein synthesis (TP), and cell morphology (scanning electron microscopy) were evaluated. Gene expression of collagen type I (Col-I) was analyzed by quantitative polymerase chain reaction (PCR). Data were analyzed by the Mann-Whitney test with a 5% significance level. Results: Higher cell viability (21.8%) occurred when the cells were irradiated with 630 nm LED at 25 J/cm2 . Concerning TP, no statistically significant difference was observed between irradiated and control groups. A significant increase in ALP activity was observed for all tested LED parameters, except for 450 nm at 4 J/cm2 . Quantitative PCR showed a higher expression of Col-I by the cells subjected to infrared LED irradiation at 4 J/cm2 . More attached cells were observed on dentin discs subjected to irradiation at 25 J/ cm2 than at 4 J/cm2 . Conclusion: The infrared LED irradiation at an energy density of 4 J/cm2 and red LED at an energy density of 25 J/cm2 were the most effective parameters for transdentinal photobiomodulation of cultured odontoblast-like cells.
Keywords: LED; Odontoblast-like cell; Phototherapy; Dentin; Wavelenghts